From bench to bedside: evolution of anti-TNFalpha therapy in rheumatoid arthritis - Maini, Ravinder (Henry Stewart Talks, 2009)
What are cytokines?, Early experiments, Human cytokines in the 1980s, Identification of TNFalpha at protein and genomic level, TNFalpha and anti-TNFalpha antibodies, Rheumatoid arthritis (RA): burden of disease, Pathology of RA, IL-1 and TNFalpha, Cytokine cascade in RA, A molecular hypothesis, First anti-TNF (cA2/infliximab) in clinical trials in RA, How does anti-TNF work?, Why is cellularity reduced?, Anti-TNF therapy inhibits cartilage and especially bone destruction, Infliximab regulates altered T and B cell immunity, Biological effects of Infliximab, Anti-TNF biologicals in the lab, Efficacy in randomized clinical trials, Effective anti-TNF therapy demonstrates shared TNF-pathways in other diseases, Adverse events and safety issues, Limitations of anti-TNF therapy, After TNF: what are we looking for?